Marks' basic medical biochemistry a clinical approach - Lieberman, Michael; Peet, Alisa (Wolters Kluwer, 2018)
Connect biochemistry to clinical practice!" Marks' Basic Medical Biochemistry links biochemistry to physiology and pathophysiology, allowing students to apply fundamental concepts to the practice of medicine - from diagnosing patients to recommending effective treatments